2018
DOI: 10.1155/2018/5632650
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold Periodic Signal Detection by Bounded Noise‐Induced Resonance in the FitzHugh–Nagumo Neuron

Abstract: Neurons can detect weak target signals from complex background signals through stochastic resonance (SR) and vibrational resonance (VR) mechanisms. However, random phase variation of rapidly fluctuating background signals is generally ignored in classical VR or SR studies. Here, the rapidly fluctuating background signals are modeled by bounded noise with random rapidly fluctuating phase derived from Wiener process. Then, the influences of bounded noise on the weak signal detection are discussed in the FitzHugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 54 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…According to the literature, a growing number of studies indicated that the noise generated by randomly channel opening limits neuronal response reliability 32 , influences the energy efficiency of channels 33 , and constrained the physical dimensions of axon diameters 34 . Conversely, noise can have a beneficial role by enhancing the detection of weak periodic signals via pseudo-stochastic resonance mechanism 35 or via enhancing subthreshold oscillations 36 . Consequently, it seemed that the magnitude of the channel noise is under evolutionary pressure in the biological system seeking an energy-efficiency coding system 37 .…”
Section: Pseudo Resonance Between Brain and Neuron Cordsmentioning
confidence: 99%
“…According to the literature, a growing number of studies indicated that the noise generated by randomly channel opening limits neuronal response reliability 32 , influences the energy efficiency of channels 33 , and constrained the physical dimensions of axon diameters 34 . Conversely, noise can have a beneficial role by enhancing the detection of weak periodic signals via pseudo-stochastic resonance mechanism 35 or via enhancing subthreshold oscillations 36 . Consequently, it seemed that the magnitude of the channel noise is under evolutionary pressure in the biological system seeking an energy-efficiency coding system 37 .…”
Section: Pseudo Resonance Between Brain and Neuron Cordsmentioning
confidence: 99%
“…Since the Italian researcher Benzi [15,16] proposed the stochastic resonance (SR) concept in 1981, SR has attracted the attention of many scholars and has been widely used in the fields of image enhancement [17,18], mechanical equipment fault diagnosis [19][20][21], wireless communication [22][23][24], etc.. There are some restrictions on using the method of SR [25], and scholars have studied many ways to overcome it. Reference [26] proposed a variable-scale SR method to overcome the limitation that SR can only be used under the condition that the signal frequency is smaller than 1 Hz and increases the scope of applicable conditions for SR.…”
Section: Introductionmentioning
confidence: 99%
“…e generation and regulation mechanism of SR in the nervous system, which depends on the frequency difference, is revealed by Guo et al [30]. e SR effect in FHN neurons was detected by Yao et al [31] and stochastic multiple resonance was found in [32] in the study of coupled excitation of FHN neurons, which can effectively detect subthreshold signals. A command filter adaptive neural network control method for multi-input multioutput nonlinear systems was proposed by Yu et al [33].…”
Section: Introductionmentioning
confidence: 99%